Cortical disconnection of the ipsilesional primary motor cortex is associated with gait speed and upper extremity motor impairment in chronic left hemispheric stroke. Issue 1 (5th October 2017) - Peters, Denise M.; Fridriksson, Julius; Stewart, Jill C.; Richardson, Jessica D.; Rorden, Chris; Bonilha, Leonardo; Middleton, Addie; Gleichgerrcht, Ezequiel; Fritz, Stacy L.
Abstract: Advances in neuroimaging have enabled the mapping of white matter connections across the entire brain, allowing for a more thorough examination of the extent of white matter disconnection after stroke. To assess how cortical disconnection contributes to motor impairments, we examined the relationship between structural brain connectivity and upper and lower extremity motor function in individuals with chronic stroke. Forty‐three participants [mean age: 59.7 (±11.2) years; time poststroke: 64.4 (±58.8) months] underwent clinical motor assessments and MRI scanning. Nonparametric correlation analyses were performed to examine the relationship between structural connectivity amid a subsection of the motor network and upper/lower extremity motor function. Standard multiple linear regression analyses were performed to examine the relationship between cortical necrosis and disconnection of three main cortical areas of motor control [primary motor cortex (M1), premotor cortex (PMC), and supplementary motor area (SMA)] and motor function. Anatomical connectivity between ipsilesional M1/SMA and the (1) cerebral peduncle, (2) thalamus, and (3) red nucleus were significantly correlated with upper and lower extremity motor performance ( P ≤ 0.003). M1–M1 interhemispheric connectivity was also significantly correlated with gross manual dexterity of the affected upper extremity ( P = 0.001). Regression models with M1 lesion load and M1 disconnection (adjusted for time poststroke) explained a significant amount of variance in upper extremity motor performance ( R 2 = 0.36–0.46) and gait speed ( R 2 = 0.46), with M1 disconnection an independent predictor of motor performance. Cortical disconnection, especially of ipsilesional M1, could significantly contribute to variability seen in locomotor and upper extremity motor function and recovery in chronic stroke. Hum Brain Mapp 39:120–132, 2018 . ©2017 Wiley Periodicals, Inc.